Bruno Schulz i muzyka. Exordium - Skrzypczyk, Aleksandra (Przestrzenie Teorii, 2020)
The aim of the article is to answer the question whether there are any connections between Bruno Schulz’s prose and the art of sounds, and how music is present in his prose. It is also the first recognition of this issue in his work, compiling the previous fragmentary opinions of scholars of Schulz’s work on this subject.